Pengaruh Kegiatan Ekstrakurikuler Rohani Islam (Rohis) Terhadap Hasil Belajar PAI Siswa Kelas XI SMA Dwiwarna (Boarding School) Bogor - Maspiah, Maspiah Perdani Rizky Yanthi; Indriya; Triwoelandari, Retno (Jurnal Dirosah Islamiyah, 2024)
This study was carried out with several objectives, namely: 1) To find out the PAI learning outcomes of students who participated in rohis extracurricular at Dwiwarna High School (Boarding School) Bogor, 2) To find out the PAI learning outcomes of students who did not participate in rohis extracurricular at Dwiwarna High School (Boarding School) Bogor, 3) To find out the significant difference in PAI learning outcomes of students who participated in rohis extracurricular and PAI learning outcomes of students who did not participated in rohis extracurricular activities at SMA Dwiwarna (Boarding School) Bogor. The method used in this study is quantitative. In this study, an expost facto type of research is used. The techniques used are observation, questionnaire and documentation. The number of respondents in this study was 30 students. This research is in a data analysis technique using an independent sample t test. The results of the study show that: 1) The learning outcomes of PAI students who take part in extracurricular received a score with a good category with an average of 86.16% 2) Learning outcomes that did not take part in the rohis extracurricular received a score with a good category with an average of 79.12%. 3) based on the calculation of the Independent Sample t test on the learning results of PAI saw the results of Sig.(2-tailed) of 0.000 < 0.05. Thus, it can be said that there is a difference between the learning outcomes of PAI students in grade XI who participate in the extracurricular rohis and the learning outcomes of PAI students in grade XI who do not participate in the extracurricular of the rohis.